Zeolites and Metal-Organic Frameworks - Blay, Vincent; Bobadilla, Luis Francisco; Cabrera García, Alejandro (Atlantis Advances in Nanotechnology, Material Science and Energy Technologies, 2018)
Zeolites are natural or synthetic materials with porous chemical structures that are valuable due to their absorptive and catalytic qualities. Metal-Organic Frameworks (MOFs) are manmade organometallic polymers with similar porous structures. This introductory book, with contributions from top-class researchers from all around the world, examines these materials and explains the different synthetic routes available to prepare zeolites and MOFs. The book also highlights how the substances are similar yet different and how they are used by science and industry in situations ranging from fueling cars to producing drugs.